Motivation Employees Of Sri Lanka Railways For Better Performances Through Concentration And Mindfulness In The Noble Eight Fold Path In Buddhism - Samarasinghe, Wijaya (Advances in Social Sciences Research Journal, 2018)
According to Buddhism, It can be identified two objectives as long term and short term in Buddhist counselling related to the Employees. The long-term objective of counseling is to cessation of such suffering by attaining Nibbana. The main focus of this study is investigating how the Buddhist counseling can help employees to unload their work-related burden and create conducive environment for employment by studying whether employees could be motivated by the Concentration and Mindfulness in noble eightfold path in order to enhance its performances. Concentration and mindfulness is significantly important in employee counseling. In this study, it was studied whether concentration and mindfulness in noble eight-fold path could motivated employee counseling at the SLR as concentration is exclusive and settle down with one item while ignoring all others, whereas mindfulness in inclusive which focus of attention and watches with a broad area. Accordingly, Noble eight-fold –concentration and mindfulness in relation to the employee counseling was measured and the summary of the analysis of data it could be concluded that sixty one percent of employees were aware to practice concentration in their job-related matters and 39 percent of them were strangers to the importance of concentration and fifty eight percent of employees were aware of the importance of mindfulness in their job-related matters and 42 percent of them were strangers to the important of mindfulness. Therefore, it can be concluded that the employees of the SLR could be motivated by the Buddhist way of counseling to enhance their performances.